Aspirations and Challenges in Regard to the Electronic Litigation in Light of the Latest Adjustement - Benaired, Abdelghani; Bediaf, Hadjer (Journal of Legal Studies and Researches, 2021)
The world has recently witnessed a digital revolution that impacted all fields One of the directly impacted fields is the judicial field. The present research paper aims to study the electronic litigation in the Algerian judicial system, specifically to address its positive sides, as well as the negative sides that could result from it the study concluded that electronic litigation is considered as effective if legal and material means are available. However it may result in violations of the rights of individuals if it is not implemented in an optimal manner.